INDEKS VEGETASI KAWASAN SUAKA ALAM GUNUNG MARAPI SUMATERA BARAT TAHUN 2009-2019 - Afdhal Afdhal; iswandi U (DEPARTEMEN GEOGRAFI FIS UNP, 2019)
ABSTRACT Vegetation mapping aims to see the changes that occur from 2009 to 2019 and also compare the accuracy of methods of image interpretation of vegetation. The method used to detect vegetation density is the NDVI transformation method and the TVI transformation. This study aims to, 1) Determine the level of vegetation density using vegetation transformation NDVI and TVI transformation. 2) To identify changes in the area of ​​vegetation in West Sumatra's Mount Marapi Nature Reserve in 2009-2019. 3) comparing the NDVI transformation and TVI transformation in the vegetation classification of Mount Marapi Nature Reserve in 2009-2019. NDVI (Normalized Difference Vegetation Index), TVI (Tringular Vegetation Index) on vegetation density, confusion matrix are the methods used in this study. The data used Landsat TM5 satellite imagery recording in 2005 and OLITIR in 2019. In this study obtained the results of the level of vegetation density in the 2009 NDVI transformation, of which the most extensive classification is in the classification of meetings with an area of ​​4211.12 ha, and in 2019 the most extensive classification is very tight with an area of ​​2217.56 ha. In the TVI 2009 transformation the broadest classification was the classification of meetings with an area of ​​5855.57 ha, and in 2019 the classification of meetings with an area of ​​4468,057 ha. The two methods used have differences in the level of accuracy, the NDVI transformation method has an accuracy rate of 75.5% while the TVI transformation is 80%, so the TVI method is suitable for detecting the vegetation density of Mount Marapi.